2010
DOI: 10.1007/s11664-010-1112-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron Sputter Epitaxy and Characterization of Wurtzite AlInN on Si(111) Substrates

Abstract: AlInN films were grown on Si(111) substrates by the direct-current reactive sputtering method at temperatures from 150°C to 350°C. Growth of the AlInN films was found to be c-axis oriented, and the surfaces of the films were smooth. The bandgap structures and electron mobility of the AlInN films were studied using optical reflectance spectra and the Hall-effect method, respectively. The effects of an AlN buffer layer on the microstructure and optical and electrical properties of the AlInN films were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…AlInN layers have been grown by different techniques, such as metal-organic chemical vapor deposition (MOCVD) 9) , molecular beam epitaxy (MBE) 10,11) , and sputtering deposition [12][13][14] . Among them, the sputtering technique allows the deposition of AlInN at a low substrate temperature, because of the enhanced kinetic energy of the constituent ions given by the sputtering process of the targets itself.…”
Section: Introductionmentioning
confidence: 99%
“…AlInN layers have been grown by different techniques, such as metal-organic chemical vapor deposition (MOCVD) 9) , molecular beam epitaxy (MBE) 10,11) , and sputtering deposition [12][13][14] . Among them, the sputtering technique allows the deposition of AlInN at a low substrate temperature, because of the enhanced kinetic energy of the constituent ions given by the sputtering process of the targets itself.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques such as metal organic vapor phase epitaxy (MOVPE) [10][11][12], molecular beam epitaxy (MBE) [13][14], magnetron sputtering [15][16][17][18][19], pulsed laser deposition [20] and reactive evaporation [21] have been used to grow InAlN thin films. Growth of these films using MOVPE and MBE suffers from the difficulties associated with a large difference in the growth temperatures and thermal stabilities of InN and AlN that often result in the phase separation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The films deposited using this technique show good adhesion to the substrate with high mechanical integrity and stability [23]. Previous studies regarding the growth of InAlN using magnetron sputtering indicated that by optimizing various deposition conditions such as growth temperatures, RF power, gas pressures and addition of buffer layers, structural quality of these films can be improved [15][16][17]. In a recent study, Besleaga et al [19] used reactive RF magnetron co-sputtering technique to grow Al 1-x In x N thin films (0>x<1) on the glass and polyethylene terephthalate substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reveal that this method also has the advantages in growing In-rich AlInN thin films without phase separations. [11][12][13] However, studies of AlInN for solar cell applications are still lacking in the literature. 1,8 In this letter, we report on a magnetron-sputter deposition of In-rich AlInN thin films on p-Si(001) and c-plane sapphire substrates.…”
Section: Introductionmentioning
confidence: 99%